Manipulating hydrophobicity of polyester nanofiber mats with egg albumin to enhance cell interactions. Issue 10 (12th August 2021) - Patel, Pratikshkumar R.; Pandey, Komal; Killi, Naresh; Gundloori, Rathna Venkata Naga
Abstract: A hybrid of poly‐l ‐lactic acid (PLA) and poly‐ε‐caprolactone (PCL) system was designed using hydrophilic generally regarded as safe (GRAS) protein, egg albumin (EA), and fabricated as nanofiber mats (NM) to facilitate improved cell interactions and functionality. Our studies include, preparation and analysis of physicochemical properties of NM. Surface morphology of NM was smooth with the diameter ranging from 250 to 400 nm. The contact angle of NM decreased from 80 to 45° with the increase in EA concentration. The rate and extent of swelling was increased 3‐folds with the addition of EA. Release studies of NM showed maximum amount of MTz was released with the increase in MTz concentration (>85%). The MTz interaction with EA and structure stability of EA was confirmed from fluorescence and circular dichroism studies. NM showed increase in inhibition of bacterial growth of Staphylococcus aureus and Escherichia coli with the increase in MTz concentration. Cell viability of the NM was >80% and also, the cell proliferation increased as EA content increased. NM hemolytic activity was less than 5% suggesting compatibility. Hence, results concluded that EA had regulated hydrophobicity, promoted cell interactions, and proliferation and therefore, NM is considered safe for tissue regeneration. Abstract : Influence of hydrophilicity on 3T3‐L1 cells.